PENGARUH SOSIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN DAN KEPERCAYAAN MEREK SEBAGAI VARIABEL MEDIASI STUDI KASUS CENGHAR KOPI - Setiawan, Iwan; Susilawati, Erna (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2024)
This study aims to determine the influence of Social Media Marketing on purchasing decisions through brand trust as a mediating variable on Cenghar Kopi Cimahi customers. The problem in this study is how Social Media Marketing influences Customer Purchasing Decisions through Brand Trust both directly and indirectly.This study was conducted with a quantitative approach with descriptive and verification research methods. Primary data collection was carried out by distributing questionnaires to a sample of 100 Cenghar Kopi Cimahi customers. The analysis method used in this study is the Structural Equation Modeling Partial Least Square (SEM-PLS) analysis method.The results of the study show that the Social Media Marketing variable has a significant influence on Brand Trust, while the Social Media Marketing variable has a path that does not have a significant influence on Purchasing Decisions in which means moderate, and Social Media Marketing has a significant influence on Purchasing Decisions mediated by Brand Trust. The recommendation in this study is that companies must be able to improve strategies that stimulate positive consumer Trust and focus on Social Media Marketing elements that can provide added value to brand trust and indirectly strengthen Purchasing Decisions. ABSTRAK